Metrologia dei campi di radiazioni di bassa energia - Mariotti, Francesca <1976> (Alma Mater Studiorum - Università di Bologna, 2008)
The conversion coefficients from air kerma to ICRU operational dose equivalent quantities for ENEA’s realization of the X-radiation qualities L10-L35 of the ISO “Low Air Kerma rate” series (L), N10-N40 of the ISO “Narrow spectrum” series (N) and H10-H60 of the ISO “High Air-kerma rate” (H) series and two beams at 5 kV and 7.5 kV were determined by utilising X-ray spectrum measurements. The pulse-height spectra were measured using a planar high-purity germanium spectrometer (HPGe) and unfolded to fluence spectra using a stripping procedure then validate with using Monte Carlo generated data of the spectrometer response. HPGe portable detector has a diameter of 8.5 mm and a thickness of 5 mm. The entrance window of the crystal is collimated by a 0.5 mm thick Aluminum ring to an open diameter of 6.5 mm. The crystal is mounted at a distance of 5 mm from the Berillium window (thickness 25.4 micron). The Monte Carlo method (MCNP-4C) was used to calculate the efficiency, escape and Compton curves of a planar high-purity germanium detector (HPGe) in the 5-60 keV energy. These curves were used for the determination of photon spectra produced by the X-ray machine SEIFERT ISOVOLT 160 kV in order to allow a precise characterization of photon beams in the low energy range, according to the ISO 4037. The detector was modelled with the MCNP computer code and validated with experimental data. To verify the measuring and the stripping procedure, the first and the second half-value layers and the air kerma rate were calculated from the counts spectra and compared with the values measured using an a free-air ionization chamber. For each radiation quality, the spectrum was characterized by the parameters given in ISO 4037-1. The conversion coefficients from the air kerma to the ICRU operational quantities Hp(10), Hp(0.07), H’(0.07) and H*(10) were calculated using monoenergetic conversion coefficients. The results are discussed with respect to ISO 4037-4, and compared with published results for low-energy X-ray spectra. The main motivation for this work was the lack of a treatment of the low photon energy region (from a few keV up to about 60 keV).